Handwriting Problems in the Secondary School. - Sassoon, R. (Sage Publications, 2006)
A considerable proportion of pupils leave primary school unable to write well enough to deal with the demands of secondary school. This innovative new book aims to help teachers and SENCOs to work alongside pupils to help them address their own difficulties. The book has three parts: Part one explores the various issues which underpin any discussion of handwriting: letterforms; the pros and cons of handwriting models; how to help children write at speed; writing posture; pens and pen hold; left-handedness; talking to parents; and some of the common causes of handwriting problems. Part two pres.